PEMANFAATAN LIMBAH FLY ASH DAN BOTTOM ASH SEBAGAI CAMPURAN BETON - Hestianita, Devie (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2024)
ABSTRACT : PLTU waste produces a large enough amount that requires management so as not to cause environmental problems. In the field of construction, fly ash and bottom ash have the potential to be developed, one of which is their use as a base material. Potential if developed, one of which is its use as a basic ingredient in the concrete making mixture. This research aims to determine the percentage of increase or decrease in compressive strength of concrete produced with the addition of fly ash and bottom ash with a variation of 0%. Fly ash and bottom ash have variation of 0%, 7.5%, 15%, and 22.5%, with the age of 14 days, 21 days, and 28 days. 14 days, 21 days, and 28 days for each combination of mixtures with a plan quality of K-250 and know the comparison of compressive strength of concrete without mixtures and using a mixture of fly ash and bottom ash. Based on the research showed that the substitution of fly ash as cement and bottom ash as fine aggregate with a percentage of 0%, 7.5%, 15%, and 22.5%, the compressive strength of days-old concrete was 236 kg/cm2, 193 kg/cm2, 175 kg/cm2, 148 kg/cm2, 21 days-old concrete compressive strength values of 168 kg/cm2, 257 kg/cm2, 210 kg/cm2, 185 kg/cm2 and the compressive strength of concrete aged 28 days by 324 kg/cm2, 281 kg/cm2, 237 kg/cm2, 212 kg/cm2. The existence of the substitution of fly ash and bottom ash to normal concrete by 7.5%, 15%, and 22.5% decreased in strength as percentage of fly ash substitution to cement and bottom ash to normal concrete increased. Fly ash is to cement, and bottom ash is to sand. The greater the substitution of fly ash and bottom ash substitution to normal concrete, the more the strength of concrete descreased due to the reduced compositon of fine aggregate gradation and cement to normal concrete. Keywords : Concrete, Compressive Strength, Fly Ash, Bottom Ash ABSTRAK: Limbah PLTU ini menghasilkan jumlah yang cukup besar sehingga memerlukan pengelolaan agar tidak menimbulkan masalah lingkungan. Dalam bidang kontruksi abu terbang (fly ash) dan abu dasar (bottom ash) merupakan suatu hal yang sangat potensial bila dikembangkan, salah satu penggunaannya sebagai bahan dasar campuran pembuatan beton. Penelitian ini bertujuan untuk mengetahui persentase peningkatan atau penurunan kuat tekan beton yang dihasilkan dengan tambahan fly ash dan bottom ash dengan variasi sebesar 0%, 7,5%, 15%, dan 22,5% dengan umur 14 hari, 21 hari serta 28 hari untuk setiap kombinasi campuran dengan mutu rencana K-250 dan mengetahui perbandingan kuat tekan beton tanpa campuran dan memakai campuran fly ash dan bottom ash. Berdasarkan dari hasil penelitian dengan substitusi fly ash sebagai semen dan bottom ash sebagai agregat halus dengan persentase 0%, 7,5%, 15%, dan 22,5%, diperoleh nilai kuat tekan beton umur 14 hari sebesar 236 kg/cm2, 193 kg/cm2, 175 kg/cm2, 148 kg/cm2, nilai kuat tekan beton umur 21 hari sebesar 168 kg/cm2, 257 kg/cm2, 210 kg/cm2, 185 kg/cm2 dan nilai kuat tekan beton umur 28 hari sebesar 324 kg/cm2, 281 kg/cm2, 237 kg/cm2, 212 kg/cm2. Adanya subsitusi fly ash dan bottom ash terhadap beton normal sebesar 7,5%, 15%, dan 22,5% mengalami penurunan kekuatan seiring bertambahnya persentase substitusi fly ash terhadap semen dan bottom ash terdahap pasir. Semakin besar substitusi fly ash dan bottom ash terhadap beton normal, semakin menurun kekuatan beton disebabkan karena berkurangnya komposisi gradasi agregat halus dan semen terhadap beton normal.Kata Kunci : Beton, Kuat Tekan, Fly Ash, Bottom Ash